Do patients with hallucinations imagine speech right?. (September 2020) - Altamura, Mario; Prete, Giulia; Elia, Antonella; Angelini, Eleonora; Padalino, Flavia A; Bellomo, Antonello; Tommasi, Luca; Fairfield, Beth
Abstract: A direct relationship between auditory verbal hallucinations (AVHs) and decreased left-hemispheric lateralization in speech perception has been often described, although it has not been conclusively proven. The specific lateralization of AVHs has been poorly explored. However, patients with verbal hallucinations show a weak Right Ear Advantage (REA) in verbal perception compared to non AVHs listeners suggesting that left-hemispheric language area are involved in AVHs. In the present study, 29 schizophrenia patients with AVHs, 31 patients with psychotic bipolar disorder who experienced frequent AVHs, 27 patients with schizophrenia who had never experienced AVHs and 57 healthy controls were required to imagine hearing a voice in one ear alone. In line with previous evidence healthy controls confirmed the expected REA for auditory imagery, and the same REA was also found in non-hallucinator patients. However, in line with our hypothesis, patients with schizophrenia and psychotic bipolar disorder with AVHs showed no lateral bias. Results extend the relationship between abnormal asymmetry for verbal stimuli and AVHs to verbal imagery, suggesting that atypical verbal imagery may reflect a disruption of inter-hemispheric connectivity between areas implicated in the generation and monitoring of verbal imagery and may be predictive of a predisposition for AVHs. Results also indicate that the relationship between AVHs and hemispheric lateralization for auditory verbal imagery is not specific to schizophrenia but may extend to other disorders as well. Highlights: Patients with hallucinations show no lateral bias for auditory imaging. Schizophrenia may be the consequence of a failure in brain lateralization. Atypical verbal imagery may be predictive of a disposition to auditory verbal hallucinations.